Riding with the ants - Duarte, A. P.M. [UNESP]; Attili-Angelis, D. [UNESP]; Baron, N. C. [UNESP]; Groenewald, J. Z.; Crous, P. W.; Pagnocca, F. C. [UNESP] (Westerdijk Fungal Biodiversity Institute, 2017)
Isolates of Teratosphaeriaceae have frequently been found in the integument of attine ants, proving to be common and diverse in this microenvironment. The LSU phylogeny of the ant-isolated strains studied revealed that they cluster in two main lineages. The first was associated with the genus Xenopenidiella whereas the other represented two ant-isolated lineages sister to the taxa Penidiella aggregata and P. drakensbergensis, which are allocated to the new genus Penidiellomyces. The genus Penidiella is limited to the lineage containing P. columbiana, which is not congeneric with Penidiellomyces or Penidiellopsis, nor with Simplicidiella, a novel genus introduced here to accommodate a strain isolated from ants. For species level analysis, the final 26 aligned sequences of the ITS (498 characters), cmdA (389 characters), tef1 (342 characters) and tub2 (446 characters) gene regions lead to the introduction of six new species in Xenopenidiella, and one in respectively Penidiellopsis and Simplicidiella. The species described in this study were distinguished by the combination of morphological and phylogenetic data. Novelties on the integument of leaf-cutting ants from Brazil include: Penidiellopsis ramosus, Xenopenidiella clavata, X. formica, X. inflata, X. laevigata, X. nigrescens, X. tarda spp. nov., and Simplicidiella nigra gen. & sp. nov. Beta-tubulin is recommended as primary barcode for the distinction of species in Penidiellopsis, whereas ITS was sufficient to distinguish species of Xenopenidiella.
Keywords: Attini tribe; Leaf-cutting ants; Multi-gene analyses; Systematic; Xenopenidiella